International Trade as an “Integrated Equilibrium”: New Perspectives - Davis, Donald R; Weinstein, David E (American Economic Review, 2000)
The integrated equilibrium is a paradigm that has played a central role in the field of international trade. The concept originated with Paul A. Samuelson (1949), was further developed by Avinash K. Dixit and Victor F. Norman (1980), and placed at the heart of international analysis by Elhanan Helpman and Paul R. Krugman (1985). The central idea is that a world with imperfect mobility of productive factors across regions or countries may replicate the essential equilibrium of a fully integrated economy, provided that goods are perfectly mobile. The concept of the integrated equilibrium has proved to be exceptionally tractable and useful for analytic developments, as for example in the work of Gene M. Grossman and Helpman (1992). We have found using elements of integrated equilibrium analysis useful in our own work (e.g., Davis et al., 1997). The central figures in developing the theory of trade and growth within the integrated equilibrium framework have been quite aware of its limitations. Helpman and Krugman (1985) include a section on the cases in which factor-price equalization (FPE) breaks down. Grossman and Helpman (1992) make the distinction between national and international spillovers a key element of their theory of trade and growth. Moreover, the starting point of Krugman’s work in the past decade on economic geography has been precisely to deny that the world operates as if it were an integrated economy. This notwithstanding, we believe that the grip of integrated equilibrium analysis on the way that the economics profession conceives of world trade patterns remains very powerful and in important ways distorts one’s view of trade relations, particularly among the relatively rich countries of the OECD. We do not propose to banish integrated equilibrium analysis. We believe that it is useful in the proper context. However, we do propose that it is important to have a fuller appreciation of the limits of such analysis from an empirical standpoint and thus to have a richer view of the determinants of world trade patterns.